Perancangan Interior Gedung Konser Musik Klasik di Semarang - Widjaja, Gabriella Febe; Honggowidjaja, Stephanus Pantja; Rakhmawati, Anik (Intra, 2019)
The development of classical music in the city of Semarang has increased, both in terms of the number of musicians that continues to grow and in terms of community appreciation. However, the development of music appreciation has not been accompanied by adequate facilities for musicians to channel their talents. A building with a good and correct acoustic system is very necessary to see the situation that the show building in Semarang has not reached that yet. The design of a classical music concert hall in Semarang aims to meet the needs of musicians, especially those in the city of Semarang. Seating arrangement, accoustic system handlers with the processing of interior elements and proper material selection is carried out to create a good and even sound result. The building design styles that suit the type of music that play in the concert hall helps create a comfortable atmosphere for the audience.